0
$\begingroup$

I have the following problem:

$\int^\pi_0 (4y^2-y'^2)dx$

which satisfies: $y=1$ on $x=0$ and $y'=0$ on $x=\pi$.

I am to show that the solution is $y=cos(2x)$.

Now, I first realised that the integrand is a function of $y$ and $y'$ only, so the usual Euler-Lagrange equation can be written as (where f is the integrand):

$f-y'\dfrac{\partial f}{\partial y'} = c_1$

(follows from $\dfrac{\partial f}{\partial y} - \dfrac{d}{dx} \dfrac{\partial f}{\partial y'} = 0$).

Now, if I substitute the terms in, this gives me:

$\dfrac{dy}{dx} = \sqrt{c_1-4y^2}$

Which, after separation of variables, gives me:

$\dfrac{\sin^{-1}(2y/\sqrt{c_1})}{2} = x + c_2$

Now, solving this with the given initial conditions gives me $y=1$, not $y=cos(2x)$.

Anyone able to point me in the right direction here?

$\endgroup$
1
$\begingroup$

Following from your second last equation,

$$y = \frac{\sqrt{c_1}}{2}\sin(2(x + c_2))$$

The two conditions $f(0) = 1$, $f'(\pi) = 0$ imply $$\frac{\sqrt{c_1}}{2}\sin(2c_2) = 1 \ \ \ \ \ \ \ \ \ \ \ \ -- (1)$$ $$\sqrt{c_1}\cos(2\pi + 2c_2) = \sqrt{c_1}\cos(2c_2) = 0 \ \ \ \ -- (2) $$

One solution for $c_2$ from $(2)$ is $c_2 = \pi/4$ and then from $(1)$, $c_1 = 4$. Thus

$$y = \sin(2x + 2c_2) = \sin(2x + \pi/2) = \cos(2x)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.